1998
DOI: 10.1021/la9808420
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble, Isolable Gold Clusters Protected by Tiopronin and Coenzyme A Monolayers

Abstract: Isolable, water-soluble gold clusters protected by monolayers of tiopronin (tiopronin−MPCs) or coenzyme A (CoA−MPCs) were synthesized by a procedure of comparable simplicity to the Brust synthesis for alkanethiolate monolayer-protected gold clusters. High-resolution transmission electron microscopy shows that, like their alkanethiolate−MPC counterparts, the average core diameters of tiopronin−MPCs can be systematically controlled by varying the tiopronin:Au mole ratio employed in the reaction. The UV−vis spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
457
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(493 citation statements)
references
References 30 publications
(100 reference statements)
34
457
1
1
Order By: Relevance
“…Tiopronin, a thio-containing compound, was used for this purpose. It has been used to treat cystinuria and rheumatoid arthritis and as capping ligand for the synthesis of gold nanocluster [24,25]. We found that adding tiopronin to concentration of 1 mM in BGE was optimal for the analysis.…”
Section: Resultsmentioning
confidence: 96%
“…Tiopronin, a thio-containing compound, was used for this purpose. It has been used to treat cystinuria and rheumatoid arthritis and as capping ligand for the synthesis of gold nanocluster [24,25]. We found that adding tiopronin to concentration of 1 mM in BGE was optimal for the analysis.…”
Section: Resultsmentioning
confidence: 96%
“…Colloidal gold synthesis is well understood, and there are a variety of known synthetic preparation methods based in both aqueous and organic solvent systems that span a range of sizes from a few nanometers up to about a tenth of a micron. [11][12][13] In addition, colloidal gold has a history of use in biological and medical applications with no known inherent cytotoxicity. 10,14,15 Colloidal gold's high electron density allows its direct imaging via electron microscopy and its unique surface plasmon resonance properties provide a convenient handle on the aggregation state of the colloid.…”
Section: Introductionmentioning
confidence: 99%
“…10,14 Colloidal gold reacts selectively and covalently with thiol or disulfide-containing reagents, allowing a straightforward route to covalent ligand-gold conjugation for surface chemistry manipulation or targeting purposes. 12,13,16,17 Finally, it may also be possible to display targeting groups on the surface of the colloidal gold particles by simple direct physical adsorption. 15 Many investigators of nonviral gene scaffolds have used the charge ratio, or ratio of cations to anions in a formulation, to quantify the amount of polycationic carrier relative to the amount of DNA in their complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Simard et al (2000) developed a synthesis method that we have used to produce gold NPs simultaneously capped with both octanethiol and thiolated undecanoic acid molecules (sample labelled Au-SC 8 /SC 11 COOH). Finally, following the synthesis method presented by Templeton et al (1999), we have synthesized water soluble gold NPs capped with tiopronin (Au-ST), which is a synthetic thiol-containing biomolecule.…”
mentioning
confidence: 99%